Regulation of Lipid Signaling by Diacylglycerol Kinases during T Cell Development and Function - Krishna, Sruti; Zhong, Xiao-Ping (Frontiers in Immunology, 2013)
Diacylglycerol (DAG) and phosphatidic acid (PA) are bioactive lipids synthesized when the T cell receptor binds to a cognate peptide-MHC complex. DAG triggers signaling by recruiting RasGRP1, PKCθ and other effectors, whereas PA binds to effector molecules that include mTOR, SHP1 and Raf1. While DAG-mediated pathways have been shown to play vital roles in T cell development and function, the importance of PA-mediated signals remains less clear. The diacylglycerol kinase (DGK) family of enzymes phosphorylates DAG to produce PA, serving as a molecular switch that regulates the relative levels of these critical second messengers. Two DGK isoforms, α and ζ, are predominantly expressed in T lineage cells and play an important role in conventional αβ T cell development. In mature T cells, the activity of these DGK isoforms aids in the maintenance of self-tolerance by preventing T cell hyper-activation and promoting T cell anergy. In this review, we discuss the roles of DAG-mediated pathways, PA-effectors and DGKs in T cell development and function. We also highlight recent work that has uncovered previously unappreciated roles for DGK activity, for instance in invariant NKT cell development, anti-tumor and anti-viral CD8 responses, and the directional secretion of soluble effectors.